An anthropometric survey of US pre-term and full-term neonates - Susan M. Abdel-Rahman; Ian M. Paul; Paula Delmore; Laura James; Laura Fearn; Andrew M. Atz; Brenda B. Poindexter; Amira Al-Uzri; Andrew Lewandowski; Barrie L. Harper; P. Brian Smith; for the Best Pharmaceuticals for Children Act - Pediatric Trials Network (Taylor & Francis Group, 2017)
Background: Anthropometric data prove valuable for screening and monitoring various medical conditions. In young infants, however, only weight, length and head circumference are represented in publicly accessible databases. Aim: To characterise length and circumferential measures in pre-term and full-term infants up to 90 days post-natal. Subjects and methods: In eight US medical centres, trained raters recorded humeral, ulnar, femoral, tibial and fibular lengths along with mid-upper arm, mid-thigh, chest, abdominal and neck circumference. Data were pooled by post-menstrual age into 1-week intervals and population curves created using the lambda, mu and sigma (LMS) method. Goodness-of-fit was assessed by examining de-trended quantile-quantile plots, Q statistics and fitted centiles overlaid on empirical centiles. Results: In total, 2097 infants were enrolled in this study with a mean ± SD gestational age and post-natal age of 37.1 ± 3.3 weeks and 27.3 ± 25.3 days, respectively. A re-scale option was used to describe all curves. The resultant models reliably characterised anthropometric measures from 33-52 weeks PMA, with less certainty at the extremes (27-55 weeks). Conclusion: The population curves generated under this investigation expand existing reference data on a comprehensive set of anthropometric traits in infants through the first 90 days post-natal.